1970
DOI: 10.1111/j.1744-6570.1970.tb01657.x
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of the In‐basket Test as a Measure of Managerial Performance

Abstract: The In-Basket TestThe In-Basket Test is a simulation exercise requiring the performance of a managerial position by dealing with the mail and related items which have presumably accumulated in the "Inbasket" of the manager. Each subject is confronted with a standard set of problems in the form of letters, memos, reports, and related materials. The exercise provides an excellent training tool for prospective managers, and it is widely used for this purpose in industry. I n addition, several methods of scoring p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

1972
1972
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 2 publications
(4 reference statements)
0
29
1
Order By: Relevance
“…They note that managers may be more concerned with avoiding failures than selecting success, a procedure which results in emphasizing functional knowledge and experience at the expense of abilities. As noted earlier, Meyer (144) reported that in basket performance is independent of experience. Similarly, Fiedler (74) suggests that leadership behavior and prior supervisory experience also are generally unrelated.…”
Section: Management Selectionmentioning
confidence: 87%
See 1 more Smart Citation
“…They note that managers may be more concerned with avoiding failures than selecting success, a procedure which results in emphasizing functional knowledge and experience at the expense of abilities. As noted earlier, Meyer (144) reported that in basket performance is independent of experience. Similarly, Fiedler (74) suggests that leadership behavior and prior supervisory experience also are generally unrelated.…”
Section: Management Selectionmentioning
confidence: 87%
“…Crooks (46) presents an interesting and informative description of in-basket development and validation procedures. Meyer (144) found significant and practical relation ships between in-basket performance and on-the-job administrative per formance. Interestingly, he indicates that the abilities measured by this technique are independent of actual supervisory or administrative experience.…”
Section: Management Selectionmentioning
confidence: 98%
“…In Studies 1 and 2, both laboratory experiments, we assigned participants to a mid-level management position in a simulated company. In both studies, we used in-basket exercises, a popular tool to assess managerial behavior (e.g., Meyer, 1970;Whetzel, Rotenbury, & McDaniel, 2014) and asked the leader to respond to employee misconduct (see Hoogervorst, De Cremer, & Van Dijke, 2010 for a similar procedure). We manipulated the intentionality of the transgression (Leunissen et al, 2013;Struthers et al, 2008) GETTING IT DONE RIGHT 9 and construal level of the leader (Freitas, Gollwitzer, & Trope, 2004;McCrea, Wieber, & Myers, 2012) using existing procedures.…”
Section: Getting It Done Rightmentioning
confidence: 99%
“…Other studies provide empirical support for statements of the constructs assessed. For example, Meyer () found that a factor analysis of in‐basket ratings produced two major performance dimensions: supervision and planning/administration. Tett and Jackson () found that six behaviors were reliably measured with an in‐basket: delegating, seeking advice, following advice, requesting to meet with an individual, seeking nonadvisory information, and asking to be kept informed as to how a problem is developing.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the work samples studied in Roth et al's meta‐analysis included a variety of physical performance tasks, such as machinist tests for general vehicle mechanics (Engel, ) and psychomotor tests, such as typing (West & Bolanovich, ) and operating a sewing machine (Blum, ). Because Roth et al included only one in‐basket validity study in their meta‐analysis (Meyer, ), and because the in‐basket is quite different from the other physically oriented work samples, their validity estimate says little about the validity of the in‐basket. Because the current research is specific to in‐baskets, it provides an important contribution to the work simulation literature, in general, and the in‐basket literature, in particular.…”
Section: Introductionmentioning
confidence: 99%